Neither 'Free' nor 'Equal' Work: A Marxist-Feminist Perspective on Prostitution. Issue 1 (June 2016) - Bhattacharya, Malini
This article has been written as an intervention into the on-going debate on the decriminalization of commercial sex and uses some of the writings of Marx and Engels as a starting point for the inquiry into the relationship between the so-called 'sex-work' and other kinds of work within the capitalist system. From a brief analysis of the evolution of commercial sex in human society, of the question of choice for the woman involved in the trade and its links with trafficking networks particularly in the neo-liberal era, the article seeks to show that licensing of sex trade cannot empower the women caught up in its toils, but can only make the system more exploitative than before.